Interaction and Autonomy in Foreign Language and Culture Studies - Putistina, Olga Vladimirovna; Kvasyuk, Elena Nikolaevna; Savateeva, Oksana Viktorovna (Journal of History Culture and Art Research, 2019)
The article focuses on the problem of developing interactive and autonomous skills of the future teachers of foreign language and culture within the university educational programme. The study evaluates the effectiveness of interactive activities in promoting learners’ autonomy of pre-service teachers in the course of English language and culture studies at university and provides teaching tips for implementing the interactive model in language teachers’ education. The research adopted a pretest-posttest quasi-experimental method design and the effectiveness of interactive language classroom model was measured against a traditionally taught class with the help of self-evaluation charts based on a Likert-type scale. The findings of the experimental teaching revealed a higher level of self-beliefs of respondents of the experimental group about the development of their autonomous skills and professional confidence in their education in foreign language and culture, which indicated the effectiveness of interactive activities in developing learners’ autonomy and a correlation between interaction and autonomy in linguistic and cultural studies. It was concluded in the experimental study that autonomy as a personal characteristic can be developed through interactive practice in and outside the classroom, and the interactive model of teaching can be successfully integrated into the concept of autonomous language and culture studies.